The Influence Of Non-AI And AI-Generated Tiktok True Story Content On Generation Z's Perceptions (A Study On Elaboration Likelihood Theory): - - Nadia Agustina Rahayu; Ratih Hasanah Sudjradjat (INJECT (Interdisciplinary Journal of Communication), 2025)
This study aims to determine the effect of TikTok True Story non-AI content and AI content on Generation Z's perceptions. This research is important considering the widespread use of artificial intelligence technology in digital content creation, which can affect the way audiences understand and assess information. The method used is quantitative with a descriptive approach, and data collection through online questionnaires to 200 respondents aged 19-28 years who follow TikTok accounts @ngmare (Non-AI content) and @aiwitness.id (AI content). The results show that both Non-AI and AI content have a positive and significant effect on the perception of Generation Z, with the effect of Non-AI content of 0.790 and AI content of 0.767. This finding suggests that clear, authentic, and emotional content (Non-AI) is processed more through the central pathway, while AI content is more influenced by visual appeal and processed through the peripheral pathway in accordance with Elaboration Likelihood Theory.